ChemInform Abstract: Multicomponent Synthesis of Bicyclic Thiazolidinethiones and Oxazolidinones in Water. Issue 41 (7th October 2014) - Stalling, Timo; Pauly, Jan; Schmidtmann, Marc; Martens, Juergen
Abstract A novel water mediated protocol is developed to synthesize bicyclic thiazolidinethiones and oxazolidinones of different ring size.